Time Perspective Biases Are Associated With Poor Sleep Quality, Daytime Sleepiness, and Lower Levels of Subjective Well-Being Among Older Adults - Rönnlund, Michael; Carelli, Maria G. (Frontiers in Psychology, 2018)
This study examined the extent to which individual differences in time perspective, i.e. habitual way of relating to the personal past, present, and future, are associated with sleep quality and daytime sleepiness in a sample of older adults. The participants (N = 437, 60-90 years) completed the Karolinska Sleep Questionnaire (KSQ), a version of the Zimbardo Time Perspective Inventory (S-ZTPI) and two ratings of SWB (life satisfaction, happiness). Based on established relationships between dimension of time perspective and other variables (e.g. depression) and relations between negative retrospection (rumination) and negative prospection (worry) in prior studies, we expected higher scores on Past Negative and Future Negative to be linked to poor sleep quality and (indirectly) increased daytime sleepiness. Moreover, we examined the possibility that variations in perceived sleep and sleepiness during the day mediates the expected association between an aggregate measure of deviations from a so called balanced time perspective (DBTP) and subjective well-being (SWB). In regression analyses controlling for demographic factors (age, sex, work status), higher scores on Past Negative and Future Negative predicted poorer sleep quality and higher levels of daytime sleepiness. Additionally, most of the association between time perspective and daytime sleepiness was accounted for by individual differences in sleep quality. Finally, structural equation modelling yielded results consistent with the hypothesis that variations in sleep mediate part of the negative relationship between DBTP and SWB. Given that good sleep is essential to multiple aspects of health, future studies evaluating relationships between time perspective and adverse health outcomes should consider sleep quality as a potentially contributing factor.